Quand le roman s’est détourné de l’épopée - François Vanoosthuyse (Flaubert: Revue Critique et Génétique)
This study seeks to understand the motives and issues at stake in Lukács’s reception of Flaubert throughout his career as a philosopher and critic. In particular, we want to know whether there is a form of continuity beyond the rupture of 1917, or whether this hypothesis is completely invalid. From beginning to end, Flaubert is at least at the heart of a very consistent reflection on the relationship between epic and novel.